The Hubble Telescope launch - Mikoley, Kate (History just before you were born., 2019)
Examines events surrounding the launch of the Hubble Space Telescope and how placing this telescope in orbit has opened up space in ways that were not believed possible. Includes a timeline, a glossary, resources for further information, and factboxes.